Ten years countdown to hepatitis C elimination in Belgium: a mathematical modeling approach - Dana Busschots; Erwin Ho; Sarah Blach; Frederik Nevens; Homie Razavi; Brieuc Van Damme; Thomas Vanwolleghem; Geert Robaeys (BMC Infectious Diseases, 2022)
Abstract Background Chronic infection with the hepatitis C virus (HCV) remains a worldwide health problem. As a result, the World Health Organization (WHO) has set elimination targets by 2030. This study aims to examine the position of Belgium in meeting the WHO's targets by 2030. Methods A Markov disease progression model, constructed in Microsoft Excel, was utilized to quantify the size of the HCV-infected population, by the liver disease stages, from 2015 to 2030. Two scenarios were developed to (1) forecast the disease burden in Belgium under the 2019 Base and (2) see what is needed to achieve the WHO targets. Results It was estimated that the number of HCV RNA-positive individuals in Belgium in 2015 was 18,800. To achieve the WHO goals, Belgium needs to treat at least 1200 patients per year. This will only be feasible if the number of screening tests increases. Conclusions Belgium is on target to reach the WHO targets by 2030 but will have to make sustained efforts. However, eradicating HCV requires policy changes to significantly increase prevention, screening, and treatment, alongside public health promotion, to raise awareness among high-risk populations and health care providers.